The Determinants of Foreign Direct Investment in ASEAN Five - Song, Kuok Thong (2002)
Foreign Direct Investment has played an important role in the development of the ASEAN-5, mainly Malaysia, Singapore, Indonesia, Thailand and the Philippines for the past decade. Even though there is a growing knowledge of the role that FDI can play in stimulating economic growth and development, there remains a tremendous diversity in approaches of countries in their policies towards FDI, as well as a lingering skepticism in certain spheres as to the inevitability or universality of the benefits from FDI. In order to gain from FDI with little negative impact on the host country's economy, the host countries may implement a variety of policies on the MNEs. A test of cointegration between FDI and its determinants in ASEAN-5 between 1969 to 1999 was conducted using Pooled-Cross-Section and Time Series data in determining the common determinants shared among the ASEAN-5. The results show that GDP, employment rate, exchange rate, trade, and capital are highly correlated with FDI for the ASEAN countries. The Johansen and Juselius (1J) procedure was employed to test the long-run causal relationship among the determinants of FDI in the five ASEAN countries. The results from the above test show that the series for Malaysia, Indonesia and the Philippines are cointegrated and share a long';;fun of Thailand shows only three of the independent variables in the series are cointegrated and share a long-run equilibrium relationship. Singapore however could not fit into the series introduced in this study. This may be due to the fact that Singapore has a high quality and quantity of skilled labors compared to the rest of the ASEAN countries as well as a well-developed economic growth than the rest of the ASEAN countries.